Synthesized azodyes of 2-amino-1, 3, 4- thiadiazole - 5 - thiol (Baghdad Science Journal, 2011)
Several azo dyes were synthesized through coupling reaetion of some substituted phenols and B.naphthol with diazonium salt of 2- amino-1,3-4- thiadiazol -5- thiol. All the synthesized compounds during this work were characterized using some speetral data (F.TIRand UV)andM.P .2-[4 --Hydroxy napthyl-azo ] -1,3,4-Thiadiazol -5-Thiol • 2- [2-- hydroxy –4- NO2 – phenyl- azo]- 1,3,4 - Thiadiazol –5-Thiol.• 2- [3--Amino-4-Hydroxy phenyl –azo]-1,3,4 - Thiadiazol –5-Thiol. .• 2-[2--Amino-4-Hydroxy phenyl -azo]-1,3,4 - Thiadiazol –5-Thiol .• 2- [3--Amino-6- Hydroxy phenyl -azo]-1,3,4 - Thiadiazol –5-Thiol.• 2-[2-- Hydroxy- 5 – chloro – Pheny - azo]- 1,3,4 - Thiadiazol –5-Thiol .• 2- [4-- Hydroxy phenyl -azo] -1,3,4 - Thiadiazol –5-Thiol .• 2- [ 3-- Bromo – 6 -- Hydroxy - phenyl –1-azo] – 1,3,4, Thiadiazol –5-Thiol .